STRATEGI PENGEMBANGAN BISNIS MANUFAKTUR DALAM OPTIMALISASI OPERASIONAL JARINGAN KERJA PERUSAHAAN - Jaladri, Chafid Moyo (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2024)
This study examines the phenomenon of PT. Sayap Mas Nusantara, a tobacco manufacturing company in Malang Regency, which has experienced rapid growth by implementing a hybrid management model that combines labor-intensive and capital-intensive approaches. On one hand, the company utilizes advanced machine technology to achieve significant production volume, while on the other hand, it maintains labor-intensive characteristics. The main objective of this research is to evaluate the operational performance of PT. Sayap Mas Nusantara, focusing on the analysis of the business plan and the effectiveness of the established network in supporting overall business performance improvement. The research adopts a descriptive approach with a qualitative design, allowing for an in-depth exploration of the company's internal dynamics and external interactions influencing its operations. The results indicate that the established network has effectively contributed to improving business operations. Furthermore, the operational design of PT. Sayap Mas Nusantara aligns with the expectations of the company and its stakeholders in achieving strategic goals, reflected in the optimization of the business concept and the formation of a network that supports smooth operational processes. The study suggests that the company should continue to maintain synergy between technology and labor to achieve greater operational efficiency.